PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING DALAM MENINGKATKAN HASIL BELAJAR PPKN PADA SISWA KELAS V SD NEGERI 44 MALUKU TENGAH - Khalis, Nela Amalia; Ritiauw, Samuel Patra; Johannes, Nathalia Yohana (PEDAGOGIKA: Jurnal Pedagogik dan Dinamika Pendidikan, 2023)
Based on the results of initial observations at SD Negeri 44 Central Maluku on February 14 2023, the researchers found a problem, namely in the PPKn learning process for class V students at SD Negeri 44 Central Maluku. The picture was obtained that the learning process was still taking place in one direction, namely from the teacher to the students. . Teachers still deliver material directly, so students cannot experience the knowledge themselves This research aims to determine the application of the discovery learning model in improving PPKn learning outcomes in class V students at SD Negeri 44 Central Maluku. The type of research used is classroom action research. The subjects in this research were all class V students with a total of 38 students. The data obtained was analyzed using SPSS 24 to determine improvements in learning outcomes. The results of the research show that before using the discovery learning learning model, the results of the initial test with a total of 38 students who reached the KKM were 7 people and 31 others had not succeeded in reaching the KKM. And after carrying out further tests in cycle II, the final test showed an increase in learning outcomes with the results of the final test in cycle II showing that the number of students who scored > 70 was 34 students and 4 students who scored < 70 were in the medium category. This can be seen based on the normalization-gain calculation with the average pre-test value being 49.47, and the average post-test value being 0.78 and the average n-gain value being 78.22. Thus, it can be concluded that the application of the discovery learning model can improve learning outcomes for class V students at SD Negeri 44 Central Maluku.